The Study of Structural, Optical, and Dielectric Properties of Magnesium Chloride-Doped Triglycine Sulphate Ferroelectric Single Crystals - Dessale Alemu; Shita Firehun; Tizazu Abza; M. Esthaku Peter (Advances in Materials Science and Engineering)
Triglycine sulphate (TGS) and 1 and 2 mol% of magnesium chloride-doped TGS single crystals have been grown by using the slow evaporation solution method at room temperature. Pure and magnesium chloride-doped triglycine sulphate single crystals in a dimension of 12 × 12 × 5 cm3 have been grown at room temperature. The grown samples have been investigated by various characterization techniques such as single crystal X-ray diffraction, UV-VIS/NIR spectroscopy, dielectric studies, and energy dispersive X-ray analysis (EDAX). The single crystal X-ray diffraction studies revealed that both 1 and 2 mol% of MgCl2-doped TGS single crystals have been crystallized in monoclinic crystal structure with space group P21/m. The UV-VI/NIR spectra analysis confirmed that both pure and 1 and 2 mol% of MgCl2-doped TGS single crystals have wide optical transparency in the wavelength range of 236–1100 nm. The bandgap energy of both samples has been found to be 5.25 eV. The dielectric properties of the grown samples were recorded by measuring the dielectric constant as a function of temperature from 45 to 55°C with various frequencies (100 Hz – 1 MHz). The dielectric studies revealed that the dielectric constants of 1 and 2 mol% of MgCl2-doped TGS single crystals were increased with decreasing frequency and that the transition temperature was found to be 51°C. The EDAX spectrum confirmed the incorporation of MgCl2 into TGS single crystals.